2016
DOI: 10.19045/bspab.2016.50087
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between RT-PCR and ELISA assay on hepatitis C positive serum samples

Abstract: Hepatitis C Virus is an infectious entity mainly affects liver. The HCV belongs to family Flaviviridae of viruses. The virion has single stranded positive polarity RNA genome. It was identified in 1989. It is transmitted through transfusion of infected blood, homosexuality, vertical transmission, inadequately sterilized surgical or dental instruments. Different techniques for diagnosis of HCV are available like ICT, ELISA, MEIA and RT-PCR etc. The objective of this study was to find out the most sensitive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The sensitivity and specificity of both the strips are above 99% and 98%, respectively. All the positive samples on ICT were further confirmed by 3rd Generation Enzyme- Linked Immunosorbent Assay (ELISA) (EASE BN-96 TMB, Taiwan) as previously described [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity and specificity of both the strips are above 99% and 98%, respectively. All the positive samples on ICT were further confirmed by 3rd Generation Enzyme- Linked Immunosorbent Assay (ELISA) (EASE BN-96 TMB, Taiwan) as previously described [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…The sample with absorbance value greater than or equal to the cut-off value i.e. (2.00) was considered reactive for HBsAg and HCV-Ab while the sample with absorbance value less than the cut-off value was considered HBsAg and HCV-Ab negative [ 11 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative study in Peshawar city was done on three hundred samples for detection of HCV infection using ELISA, of which 14 samples were positive. These 14 samples were subsequently re-analyzed using the RT-PCR method that detected the HCV infection in only 5 samples 19 . Similarly, Kwenti et al (2011) reported that the maximum sensitivity and specificity of the RT-PCR 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In Pakistan, HCV was found as the main factor responsible for the development of liver cancer (Khan et al, 2009), and about 70% patients of HCC were found infected with HCV whereas HBV co infection has been found in 20% of HCC positive cases (Butt et al, 2013). In Pakistan, the prevalence of hepatic inflammation is alarming showing 4.8% positivity for anti HCV antibodies and for 2.5% HBV surface antigen with (Abbas, Jafri, & Hamid, 2010;Bahadar, Khan, Israr, & Ahmad, 2016). The prolonged untreated infection leads to the development of chronic liver disease that gradually progresses to fibrotic stage, cirrhosis, hepatic damage and finally HCC (Hajarizadeh, Grebely, & Dore, 2013).…”
Section: Introductionmentioning
confidence: 99%